PROFIL PENDIDIK IDEAL PADA ABAD XXI (Widyadari : Jurnal Pendidikan, 2021)
In the age of globalization, the quality of education is a top priority. Quality education is certainly capable of producing quality human resources as well. In formal education, the quality of education starts from the teaching and learning process carried out by the teacher or lecturer in the class. The teacher or lecturer has a very strategic role in producing quality students. Educators must have four competencies, namely: pedagogical competence, academic competence, personal competence, and social competence. The four competencies must be able to be understood and applied well in school. The ideal educator must mastering, understanding, and applying the four competencies. An ideal educator is certainly an educator who is idolized by students. The ideal educator is an educative figure who is the desire of every student or student.